ENHANCING STUDENTS’ READING COMPREHENSION OF HORTATORY EXPOSITION TEXTS THROUGH THE THINK-PAIR-SHARE METHOD: A CLASSROOM RESEARCH STUDY - Humaera, Sepya; Ruswandi, Riki; Hidayat, Hamdan (Universitas Islam Sumatera Utara (UISU), 2025)
This study explores the effectiveness of the Think-Pair-Share (TPS) method in improving students' reading comprehension of hortatory exposition texts. Conducted with 32 grade XI social studies students at SMA PGRI 2 Bandung, the research employed a quantitative approach using a survey design and purposive sampling. Data were collected through a validated questionnaire with 16 items rated on a five-point Likert scale. The TPS method was implemented over two cycles, and results showed significant improvements in students' reading comprehension and motivation. The average perception score was 3.78, with 65.6% of students agreeing or strongly agreeing that TPS facilitated their understanding of the text. Additionally, student motivation increased, with an average score of 3.81, reflecting enhanced engagement and active participation in learning activities. Reliability testing of the instrument yielded a Cronbach's Alpha value of 0.914, indicating high internal consistency. The study also highlighted the TPS method's ability to foster collaboration and critical thinking, as paired discussions enabled students to analyze arguments effectively and connect ideas within the text. These findings suggest that TPS is an effective strategy for improving comprehension and engagement in reading hortatory exposition texts, offering valuable insights for educators in creating interactive and collaborative learning environments.